The effect of conference brand knowledge on attendee behaviors - Lee, Jin-Soo (Kansas State University, 2006)
This study, based on customer-based brand equity (Keller, 1993), sought to identify key brand associations in brand knowledge and investigated attendees’ behaviors as evidenced in a comparison of a professional association’s major and regional conferences. The points of comparison were brand satisfaction, updated expectation of brand value (UEBV), brand trust, and attitudinal brand loyalty (ABL), especially the mediating effect of UEBV on brand trust-ABL link and the moderating effect of behavioral brand loyalty (BBL) within the brand trust-(UEBV)-brand loyalty link. To identify the proposed paths and differential effect of brand knowledge across I-CHRIE annual conference (IC) and regional CHRIE conferences (RC), this study sampled I-CHRIE members attending IC and/ or RC, using an online survey system. The response rate was 20.1% (213 out of 1,036) for IC and 19.4% (201 out of 1,036) for RC. Confirmatory factor analysis and/or structural equation modeling were used to test construct validity and hypotheses. Findings showed that professional education, staff service, site selection, and social networking are positively related to brand satisfaction, whereas brand awareness is negatively associated with it. Because brand satisfaction is a starting point in affecting UEBV, brand trust, and ABL, these four brand associations are presumed to be major sources of the differential effect of brand knowledge between IC and RC. Also, positive relationships existed on each path for brand satisfaction-UEBV, UEBV-brand trust, brand satisfaction-brand trust, and brand trust-ABL. It is especially important to look at the mediating effect of UEBV on brand satisfaction-brand trust path. UEBV was found to serve as a partial mediator on the brand satisfaction-brand trust path across the two groups. This result suggests that brand trust, the firm expectation that the brand will perform according to its promise, builds up through UEBV as well as through brand satisfaction. This study further extended the proposed theoretical model by dividing it into high and low BBL groups designed to unveil the differential characteristics or mechanisms between two groups. Except for the brand trust-ABL path, BBL was found to moderate the direct path (brand satisfaction to brand trust) and the indirect path (brand satisfaction to brand trust via UEBV). These findings support the notion that since high BBL attendees sustain longer relationships with a particular conference than low BBL attendees, high BBL attendees experience more cumulative satisfaction and update favorable expectations of brand value (through the perception of more [relational] benefits), thereby solidifying expectations about confidence in a brand (brand trust). Brand loyalty holds invaluable benefits for associations when associations in similar disciplines compete for potential attendees. Benefits from brand loyal customers lower marketing costs and increase market share and profitability. Thus, associations should build their conference marketing and management on brand loyalty by carefully designing brand associations attendees consider important. Persistent delivery of high-quality education programs, venue selection, and social networking enables associations to obtain cumulative satisfaction, UEBV, brand trust, and consequently brand loyalty. Retention of brand loyal attendees induces deep commitment to the conferences and great resistance to other conferences’ marketing strategies, thereby contributing to high revenue and market share.
Keywords: Attendee-based brand equity; Brand association; Brand trust; Brand knowledge; Business Administration, Marketing (0338); Recreation (0814)